Complementary and competitive: the impact of Chinese trade on South African manufacturing exports - Chien, Jing-Woei (School of Economics, 2016)
This paper makes use of South African industry level data to identify the effects of Chinese trade on South African manufacturing exports. It contributes to the existing literature by considering the implications of the different channels of exports identified in Kaplinsky et al. (2007) for Chinese exports. In particular, the direct complementary (positive) and indirect competitive (negative) channels are identified as the key channels for China-South Africa export relations. The impact of these channels are looked at, not only in the terms of aggregate export values, but also the extensive margin (product count). Overall, the results suggest a positive effect arising from Chinese exports. This result is, however, dulled by the negative implications of the indirect competitive channel effect on the extensive margin. A breakdown of the manufacturing sector into low and high-wage industries reveals that high-wage industries are the main recipients of benefits from Chinese exports through the direct complementary channel. Furthermore, the marginal effect of China from the rest of the world reveals a significantly positive difference in the high and low-wage industries for the aggregate export value and extensive margins respectively, while other specifications are inconclusive.